Ligand-Accelerated Asymmetric [1,2]-Stevens Rearrangment of Sulfur Ylides via Decomposition of Diazomalonates Catalyzed by Chiral Bisoxazoline/Copper Complex - Qu, Jian-Ping; Xu, Zheng-Hu; Zhou, Jian; Cao, Chun-Li; Sun, Xiu-Li; Dai, Li-Xin; Tang, Yong (Advanced synthesis & catalysis, 2009)
The first example of catalytic asymmetric [1,2]‐Stevens rearrangement reaction of 1,3‐oxathiolanes with diazomalonates has been developed and up to 90% ee is achieved by the bisoxazoline 4e/copper(II) triflate [Cu(OTf)2] complex.